Biodegradable nano black phosphorus based SDF1-α delivery system ameliorates Erectile Dysfunction in a cavernous nerve injury rat model by recruiting endogenous stem/progenitor cells - Qingfeng Fu; Lujie Song; Jitao Li; Bocun Yi; Yue Huang; Zhihong Zhang; Zhongcheng Xin; Jianqiang Zhu (Journal of Nanobiotechnology, 2023)
Abstract Stem cell (SC) therapy has been shown high prospects in erectile dysfunction (ED) treatment. Without ethical issues and risks of immune rejection and tumorigenesis of exogenous SC therapy, endogenous stem/progenitor cells (S/PCs) have a better potential for ED management, and their homing and redistribution are controlled by SDF1-α/CXCR4 axis. Considering black phosphorus nanosheet (BPNS) has emerged as an efficient and safe drug vehicle due to its large surface area, biodegradability, and the ability to retain and slowly release its loaded drugs, BPNS is utilized to load SDF1-α, a chemokine for S/PCs, to construct the BP@SDF1-α complex to efficiently recruit stem cells (SCs) by injury-site injection and thus ameliorate ED within the bilateral cavernous nerve injury (BCNI) rat models. We find that BP@SDF1-α can efficiently recruit exogenous SCs and endogenous S/PCs to corpus cavernosum and main pelvic ganglion (MPG) by local administration. Of note, ascribing to endogenous S/PCs recruitment, it also successfully alleviates ED in BCNI rat models by enhancing the protein expression levels of α-SMA, CD31, and nNOs, and eliciting less collagen deposition in the penis after its combined injection at corpus cavernosum and MPG. Thus, this study provides a new insight into the treatment of ED with endogenous S/PCs. Biodegradable Nano Black Phosphorus based SDF1-α delivery system ameliorates Erectile Dysfunction in a cavernous nerve Injury Rat Model by recruiting endogenous Stem/Progenitor cells